Faktor yang Mempengaruhi Keputusan Konsumen Dalam Membeli Sayuran di Pedagang Sayur Keliling - Shofia Nur Awami; Raphelia Handayaningrum; Istanto Istanto; Hilmi Arija Fachriyan (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
Seller vegetable are actors in the downstream agribusiness subsystem who have a role in distributing vegetable products in residential areas based on considerations to establish direct contact with consumers. This study aims to determine the characteristics of consumers who buy vegetables at mobile vegetable traders and find out what factors influence consumer decisions in Ambarawa Asri Housing in purchasing vegetables at mobile vegetable vendors. This research uses basic quantitative methods with a case study approach. The sample data taken were consumers who purchased vegetables at mobile vegetable vendors totaling 80 respondents. The method of data analysis is done by using multiple linear regression through the SPSS 25 application. The results showed that the characteristics of consumers are women who work as housewives between the ages of 46 to 55 years who are married with the last level of high school education and have 4 family members, have a monthly personal income of less than Rp 1,000,000 and the average monthly family income is between Rp 3,000,000 to Rp 4,999,999. Consumers shop daily at mobile vegetable vendors and rarely shop elsewhere and have 2 subscription merchants. The variables that significantly influence vegetable purchasing decisions are psychological factors, product factors, and distribution factors. Keywords: Vegetables, Purchasing Decisions, Seller